The Slavcleft: a three-center study of the outcome of treatment of cleft lip and palate. Nasolabial appearance - Stebel, Adam; Urbanová, Wanda; Klimova, Irena; Brudnicki, Andrzej; Dubovska, Ivana; Polackova, Petra; Kroupová, Daniela; Koťová, Magdalena; Fudalej, Piotr S (PeerJ, 2021)
Background: There is a multitude of protocols of treatment of cleft lip and palate (CLP) worldwide differing in number of operations, surgical techniques, and timings of surgeries. Despite, facial appearance in subjects with CLP is rarely ideal and residual stigmata are easy to notice in many patients irrespective of the protocol. The prospective controlled investigations are optimal for comparing effectiveness of treatment protocols. Because prospective studies are very challenging to perform in CLP field, it is reasonable to retrospectively assess different surgical protocols to identify the promising ones and then to test them in a prospective way. Methods: Our objective was to assess the nasolabial appearance in a preadolescent Slavic population with unilateral cleft lip and palate (UCLP) by using the 0-200 numeric scale with reference photographs. Patients treated in Warsaw, Poland (n = 32), Prague, Czech Republic (n = 26) and Bratislava, Slovakia (n = 17) were included in this retrospective study. Each cleft center used a unique surgical protocol. Two panels of professional raters (n = 7) and laypeople (n = 10) scored blindly the nasolabial esthetics on cropped frontal and profile images with cropped reference photograph present on the same slide. Intra- and inter-rater agreement was assessed with Cronbach's alpha, intraclass correlation coefficients, t-tests, and Bland-Altman plots. Inter-group differences were evaluated with one-way ANOVA and regression analysis. Results: The agreement within and between raters was acceptable. We found that patients treated in Warsaw, Prague, and Bratislava showed comparable nasolabial appearance on frontal and profile photographs when judged by both professional raters (p > 0.05) and laypeople (p > 0.05). Regression analysis did not identify influence of gender, group (i.e., Warsaw, Prague, and Bratislava), age at lip repair, surgeon, and age at photographic assessment on esthetic outcome (p > 0.05). Conclusion: This study showed that none of the surgical protocols showed superiority to produce good nasolabial appearance.